UNLOCKING THE POTENTIAL OF GAME BASED LEARNING EDUCATION IN JUNIOR HIGH SCHOOL INDONESIA - Subroto, Desty Endrawati; Bartoszeck, Amauri; Arsyad, Muhammad (Jurnal Kajian Pendidikan dan Psikologi, 2024)
This Study aims to reveal the Potential of Game-Based Learning (GBL) Education in Schools in Intermediate First (SMP) Indonesia. The research methods used​ are studies case with collect data via observations and interviews with teachers and students at a junior high school in Indonesia. Research results show that GBL has the potency to increase the involvement of students in learning, providing an environment of interactive and interesting learning, as well as facilitating a deeper understanding​ deep about material lessons. Implications study This indicated that GBL integration can become an effective alternative​ For increasing effective learning in Indonesian junior high schools.